2007
DOI: 10.1007/s11538-006-9184-7
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Local Competition in Stage-Structured Metapopulations: A New Mechanism of Pattern Formation

Abstract: A central question of ecology is what determines the presence and abundance of species at different locations. In cases of ecological pattern formation, population sizes are largely determined by spatially distributed interactions and may have very little to do with the habitat template. We find pattern formation in a single-species metapopulation model with quasi-local competition, but only if the populations have (at least) two age or stage classes. Quasi-local competition is modeled using an explicit resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In Section 2, we did not specify the neighborhoods or the spatial dimension of the habitat. Here we first describe the simple nearest neighbor dispersal and interaction in 1D and 2D spatial habitats used in both ecological studies by [12,47,26,30,8], and game theoretical studies initiated by [34,35]. Then we give a general form of the mean field equation and find the conditions under which the ESS can be destabilized.…”
Section: Stability Of Mixed Strategy Ess Of the Hawk-dove Gamementioning
confidence: 99%
See 1 more Smart Citation
“…In Section 2, we did not specify the neighborhoods or the spatial dimension of the habitat. Here we first describe the simple nearest neighbor dispersal and interaction in 1D and 2D spatial habitats used in both ecological studies by [12,47,26,30,8], and game theoretical studies initiated by [34,35]. Then we give a general form of the mean field equation and find the conditions under which the ESS can be destabilized.…”
Section: Stability Of Mixed Strategy Ess Of the Hawk-dove Gamementioning
confidence: 99%
“…The emergence of spatial inhomogeneity is related to the nonlocal (or quasi-local) interactions that are shown to be a mechanism for spatial pattern formation for a number of ecolgical processes [7,14,3,4,25,12,30,26,47]. In these earlier works it was shown that the spatial inhomegeniety is due to the fluctuating density of a species.…”
Section: Introductionmentioning
confidence: 99%
“…Kisdi & Utz (2005) put the model by Geritz & Kisdi (2004) in the spatially explicit context of a patchy environment and studied the formation of patterns along a chain of patches. Utz et al (2007) prolonged this work, adding a more detailed structure of the consumer population to the model and proposed an explanation to the emergence of an Allee effect.…”
Section: (I) Population Modelsmentioning
confidence: 99%
“…These riches include cyclic and chaotic behaviour with complicated bifurcation patterns, multiple attractors with fractal basins of attraction, and spatial pattern formation of various kinds (e.g. Kaneko 1990Kaneko , 1998Hastings 1993;Gyllenberg et al 1993;Doebeli 1995;Lloyd 1995;Doebeli and Ruxton 1998;Utz et al 2007). Because of this inherently complex dynamics, much work on discrete-time metapopulations falls back on numerical analysis and simulations, and hence is forced to commit to particular choices such as using the logistic map, or assuming nearest-neighbour dispersal or a Gaussian dispersal kernel.…”
Section: Introductionmentioning
confidence: 99%